Rauwolfia Serpentina: Studies on Optimum Methods of Propagation and their Effect on Production and Alkaloidal Content of Roots - Badhwar, R. L.; Beri, R. M.; Karira, G. V.; Ramaswami, S. (Indian Forester, 1963)
Results of studies on methods of propagation and their optimum time of planting, etc., up to about 1-, 2- and 3-year-old plants of Rauwolfia serpentina (Linn.) Benth. ex Kurz are given. For this purpose a statistically designed experiment was conducted. The results confirm our previous indicative findings with 1-, 2- and 3-year-old plants that root production of plants raised from seeds is much higher than that of plants raised vegetatively (root cuttings or stem cuttings). Indeed, in the first year it is about 5 times that of plants raised from stem cuttings and about 2.4 times that of plants raised from root cuttings (excluding mother roots). During the second year it is about 9 times that of Stem cuttings and 2.6 times that of root cuttings (excluding mother roots). In the third year it is about 6.5 times that of stem cuttings and about 2.5 times that of root cuttings (excluding mother roots). The transplants raised from seeds sown in April have given the highest yield of roots. There is also proportionate increase in root production according to age. The total alkaloidal content of roots was well above the I.P. and B.P.C. standard. Commercial plantations for root production are best raised from seeds sown in April, under Dehra Dun conditions